A computational investigation of the dynamic factors governing severity of head injury to pedestrians involved in e-scooter collisions - Paudel, Milan (2024)
A rapid rise in the popularity of e-scooters has brought forth an increasing number of e-scooter-related conflicts, crashes, and injuries to pedestrians in many cities. There is a pressing need to understand the factors influencing the severity of injury to pedestrians involved in e-scooter collisions. This paper investigates the dynamics of e-scooter-pedestrian collisions and presents a new method for relating the probability of severe head injury to collision speed in e-scooter-pedestrian collisions. A total of 160 computer simulations representing different collision scenarios have been analyzed. Our results have shown that e-scooter speed is the main determinant of the severity of pedestrian head injury. E-scooter speed ranging from 10 to 15 km/h is found to be critical for pedestrian safety as the probability of severe head injury rises rapidly within this speed range. Moreover, an e-scooter-pedestrian collision is more likely to cause severe head injury to the pedestrian than a bicycle-pedestrian collision within the same speed range. It has also been found that the weight of the e-scooter and the direction of impact do not have a strong influence on the collision metrics, especially on the probability of severe head injury. The study has also investigated the post-collision fall mechanism for different pedestrian profiles and the influence of different impact angles. Finally, some recommendations have been proposed, including a speed limit of not more than 11 km/h for e-scooterist on shared paths where the likelihood of pedestrian and e-scooter conflicts is higher. The recommendations could help authorities develop legislation for safe micro-mobility.